¡) Ans:
The given differential equation is
"y sin2x dx=(1+y^2+cos^2x)dy"
"\\implies y sin2x dx -(1+y^2+cos^2x)dy=0"
Which is of the form "Mdx +Ndy =0" .
Where "M=y sin2x \\ \\text{and} \\ N=-(1+y^2+cos2x)"
"=2sinxcos =sin2x"
As "\\frac{\\partial{M}}{\\partial{y}}=\\frac{\\partial{N}}{\\partial{x}}" ,Hence the given differential equation is an exact differential equation.
"\\therefore \\" The solution of the given differential equation is
"\\int_{y=const.}Mdx+\\int \\text{(only those therms of N which do not contains x)}dy"
"=\\int_{y=const.}ysin2x+\\int{-(1+y^2)}dy"
"=y\\int sin2x dx-\\int(1+y^2)dy"
"=-\\frac{ycos2x}{2}-y-\\frac{y^3}{3}+c"
Where "c" is the integration constant.
¡¡)ans :
The given differential equation is
"(xy^2-x^2)dx+(3x^2y^2+x^2y-2x^3+y^2)dy=0"
Which is of the form "Mdx+Ndy=0"
Here "M=(xy^2-x^2) \\ \\text{and} \\ N=(3x^2y^2+x^2y-2x^3+y)"
"\\therefore \\frac{\\partial{M}}{\\partial{y}}=2xy \\ \\text{and} \\ \\frac{\\partial{N}}{\\partial{x}}=6xy^2+2xy-6x^2"
"\\text{As} \\ \\frac{\\partial{M}}{\\partial{y}}\\neq \\frac{\\partial{N}}{\\partial{x}}"
Therefore ,the given differential equation is not exact.
But "\\frac{1}{M}(\\frac{\\partial{N}}{\\partial{x}}-\\frac{\\partial{M}}{\\partial{y}})=6" is a is a constant function , which may be regarded as function of y i,e "\\phi(y)," then the integration factor of given differential equation is
Multiplying by I.F. ,the given differential equation becomes
"e^{6y}(xy^2-x^2)dx+e^{6y}(3x^2y^2+x^2y-2x^3+y^2)=0..........(1)"
Which can be shown to be exact.
Therefore the required solution is
"\\int_{y=const.}e^{6y}(xy^2-x^2)dx+\\int e^{6y}y^2 dy=I_1+I_2(say)"
Where "I_1=\\int_{y=const.} e^{6y}(xy^2-x^2)dx ,I_2=\\int e^{6y}y^2dy"
"I_1=e^{6y}(\\frac{y^2x^2}{2}-\\frac{x^3}{3})."
"I_2=y^2\\int e^{6y}dy-\\int (\\frac{dy^2}{dy} (\\int e^{6y}dy))dy" by using by part.
"=\\frac{y^2e^{6y}}{6}-\\int 2y\u00d7\\frac{e^{6y}}{6}dy"
"=\\frac{y^2e^{6y}}{6}-\\frac{1}{3}y\\int e^{6y}dy+\\frac{1}{3}\\int( \\frac{dy}{dy}(\\int e^{6y}dy))dy" by using by parts.
"=\\frac{y^2e^{6y}}{6}-\\frac{1}{18}ye^{6y} +\\frac{1}{108}e^{6y}" .
Therefore the required solution of the given differential equation is
"=I_1+I_2"
"=e^{6y}(\\frac{y^2x^2}{2}-\\frac{x^3}{3})+\\frac{y^2e^{6y}}{6}-\\frac{1}{18}ye^{6y}+\\frac{1}{108}e^{6y}+k"
Where k is the integration constant.
Comments
Leave a comment